CENTS AND SENSIBILITY BY MAGIE ALDERSON (AN ANNOTATED TRANSLATION STUDY) - Yosiana, Meriska (Journal of Language and Literature, 2015)
This is an annotated translation research. The aims of this study are to find out the difficulties faced by the researcher in the process of translating the source text, and to find out the solutions in solving the problems the researcher comes across when translating the source text. The result of the research shows that there are some of words, structure of language, culture, slang, phrasal verb, and idioms that become difficulties for the researcher because there are non equivalent words in the target language. The different structure of language and culture are also become the difficulties during the process of translation. The finding is that the idioms in this research are translated as non-idioms in this research. Other findings is that there isslang in the source text which is translated into slang in the target text. The solutions to solve the difficulties in translation, the translator can use loan words, calque, and make the implicit meaning into eksplicit. Keywords: Annotated translation, Slang, Idiom translation